Targeting APRIL in the treatment of glomerular diseases - Cheung, Chee Kay; Barratt, Jonathan; Lafayette, Richard; Liew, Adrian; Suzuki, Yusuke; Tesař, Vladimír; Trimarchi, Hernán; Wong, Muh Geot; Zhang, Hong; Rizk, Dana V (Kidney international, 2024)
A proliferation-inducing ligand (APRIL) is a key member of the tumor necrosis factor superfamily of cytokines and plays a central role in B-cell survival, proliferation, and Ig class switching. Recently, there has been increasing interest in the role of APRIL and the related cytokine B-cell activating factor in several glomerular diseases, because of their importance in the above processes. The therapeutic inhibition of APRIL represents a potentially attractive immunomodulatory approach that may abrogate deleterious host immune responses in autoimmune diseases while leaving other important functions of humoral immunity intact, such as memory B-cell function and responses to vaccination, in contrast to B-cell-depleting strategies. In this review, we describe the physiological roles of APRIL in B-cell development and their relevance to glomerular diseases, and outline emerging clinical trial data studying APRIL inhibition, with a focus on IgA nephropathy where the clinical development of APRIL inhibitors is in its most advanced stage.
Keywords: Animals; B-lymfocyty; glomerulus; lidé; zvířata; Kidney Glomerulus; IgA nefropatie; Tumor Necrosis Factor Ligand Superfamily Member 13; Glomerulonephritis, IGA; protein TALL-2; B-Lymphocytes; Humans